The Search for and Discovery of Yiddishist Women - Häll, Lina (Lietuvos istorijos studijos, 2025)
On Saulė Valiūnaitė’s Doctoral Thesis “Yiddishist Women and their Contribution to the Formation and Presentation of Secular Jewishness in the Interwar Vilna“, and its Defense